Induced spawning of hatchery-raised Brazilian catfish, cachara Pseudoplatystoma fasciatum (Linnaeus, 1766) - Leonardo, AFG; Romagosa, E.; Borella, M. I.; Batlouni, SR (Elsevier B.V., 2004)
In the months of January 2001 and 2002, female cachara Pseudoplatystoma fasciatum were selected during their first and second gonadal maturation (2 years and 7 months old and 3 years and 7 months old, respectively) with an of oocyte diameter of 937.5 mum (82.5% with central nuclei and 17.5% with peripheral nuclei). Nine females in first maturation received two doses of carp pituitary extract (CPE), 0.5 mg/kg and 5.0 mg/kg; seven received two doses of human chorionic gonadotropin (hCG), 5 and 10 IU/g; five received doses of 0.5 CPE mg/kg and 5 hCG IU/g (CPE+hCG); and four received 0.9% saline (saline). Nine females from CPE and seven from hCG presented oocytes with the same diameter at the moment of oocyte release (100% with germinal vesicle breakdown and fertilization rate of 53.44 +/- 18.3 and 54.81 +/- 11.8%; larvae number of 165,330 +/- 94.1 and 158,570 +/- 20.6, respectively). The five females from CPE+hCG did not respond to the hormonal treatment. The four females from the saline group did not ovulate. In January 2002, 6 of 15 selected females that were going through the second reproductive cycle received CPE (five received hCG and four received saline), showing oocyte diameters similar to the ones in the first maturation. At stripping, CPE females had an oocyte diameter of 1062.5 mum (the hCG females had oocyte diameters ranging from 937.5 to 1125.0 mum; fertilization rates of 56.08 +/- 30.9 and 81.90 +/- 17.3%; 364,547 +/- 244 and 633,129 +/- 190, larvae, respectively). The fertilization rates and larvae number were higher in the second gonad maturation, both for CPE and hCG. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Brazilian catfish; cachara; Pseudoplatystoma fasciatum; final maturation; ovulation